Interakcije v mikorizosferi določajo dinamiko ogljika v ekosistemu bukovih gozdov - Grebenc, Tine (Zbornik gozdarstva in lesarstva, 2009)
Forest soils are the major stocks of organic carbon in terrestrial ecosystems.The dynamics of carbon in soil is closely related to soil (micro)organisms, predominantly symbiotic organisms. Key symbionts in forest soils regarding their taxonomic and functional diversity are ectomycorrhizal fungi. In the present study, we have analysed ectomycorrhizal community in beech dominated forest stands using morphological and molecular identification of ectomycorrhizae. Several new types were discovered and briefly described in soil samples taken in beech forest stands, down to 20 cm deep. Based on ectomycorrhizal type abundance, we have calculated the (static)content of total carbon in each of the type. Quantities of carbon stored in ectomycorrhizae were compared with modelled quantities of total carbon in forest soils. We summarise the role and importance of ectomycorrhizae for carbon dynamics in beech dominated forest ecosystems.
Keywords: bukev; ektomikoriza; Fagus sylvatica L.; gozdna tla; ogljik